Maths-
General
Easy

Question

Solve for x: 6 ( x + 1)= 4(1 + x over 4 ) + 6 + 3x

Hint:

  • Hint:
○ Simplify the equation.
○ Perform basic arithmetic operations to get value of x

The correct answer is: x = 2.


    • Step by step explanation:
    ○ Given:
    6 ( x + 1) = 4 ( 1 + x over 4 ) + 6 + 3x
    ○ Step 1:
    ○ Simplify:

    6 ( x + 1)= 4 ( 1 + fraction numerator 4 x over denominator 4 end fraction ) + 6 + 3x

    rightwards double arrow6x + 6 = 4 + + 6 + 3x

    rightwards double arrow6x + 6 = 4 + x + 6 + 3x

    rightwards double arrow6x + 6 = 10 + 4x

    rightwards double arrow6x - 4x = 10 - 6

    rightwards double arrow2x = 4

    rightwards double arrowx = 4 over 2

    rightwards double arrowx = 2

    • Final Answer: x = 2

    Related Questions to study

    card img

    With Turito Academy.

    card img

    With Turito Foundation.

    card img

    Get an Expert Advice From Turito.

    Turito Academy

    card img

    With Turito Academy.

    Test Prep

    card img

    With Turito Foundation.